Data processing made easy: standalone tool for automated calculation of isotope ratio from transient signals – IsoCor. Issue 11 (21st September 2022) - Tukhmetova, Dariya; Lisec, Jan; Vogl, Jochen; Meermann, Björn
Abstract : A data processing application (App) IsoCor facilitating automatic calculation of isotope ratios from transient signals was introduced. IsoCor performs baseline subtraction, peak detection, mass bias correction, isotope ratio and delta calculation. Abstract : Despite numerous advantages offered by hyphenation of chromatography and electrokinetic separation methods with multicollector (MC) ICP-MS for isotope analysis, the main limitation of such systems is the decrease in precision and increase in uncertainty due to generation of short transient signals. To minimize this limitation, most authors compare several isotope ratio calculation methods and establish a multi-step data processing routine based on the precision and accuracy of the methods. However, to the best of our knowledge, there is no universal data processing tool available that incorporates all important steps of the treatment of the transient signals. Thus, we introduce a data processing application (App) IsoCor that facilitates automatic calculation of isotope ratios from transient signals and eases selection of the most suitable method. The IsoCor App performs baseline subtraction, peak detection, mass bias correction, isotope ratio calculation and delta calculation. The feasibility and reliability of the App was proven by reproducing the results from isotope analysis of three elements (neodymium, mercury and sulfur) measured on-line via hyphenated systems. The IsoCor App provides trackability of the results to ensure quality control of the analysis.